The Calorific Value Experiment of Refuse Derived Fuel by Utilizing Residual Waste to Produce Energy - Somchay Vilaychaleun; Phoummixay Siharath; Chankhachone Sonemanivong; Biswadip Basu Mallik; Khampasith Thammathevo; Phouphavanh Khounpaserth; Vilakone Sandvilay; Souliphone Phommixay (GoAcademica Research & Publishing, 2023)
Refuse Derived Fuel (RDF) is excellent process to reuse the wastes from human activities or residual waste becomes renewable energy and also cut off the wastes volumes prior to transporting to landfill, it is an apart of supporting climate change mitigation due to waste generation and green house affect. This study is to focus on: 1. study on ratio of the waste material component to produce the RDF and, 2. testing and find out the RDF properties and calorific value of each material component. Therefore, according to the experiments found that, the mixtures of the plastics and dry leaves, plastics and papers, papers and dry leaves and plastics, papers and dry leaves indicated the calorific value are 14.91( ), 14.11( ), 15.02( ), 14.91( ) and 15.39 ( ), respectively.